Silver Nanoparticles from Annona muricata Peel and Leaf Extracts as a Potential Potent, Biocompatible and Low Cost Antitumor Tool - María G. González-Pedroza; Liliana Argueta-Figueroa; René García-Contreras; Yaiza Jiménez-Martínez; Eduardo Martínez-Martínez; Saúl A. Navarro-Marchal; Juan A. Marchal; Raúl A. Morales-Luckie; Houria Boulaiz (Nanomaterials, 2021)
Cancer is one of the most prevalent diseases in the world and requires new therapies for its treatment. In this context, the biosynthesis of silver nanoparticles (AgNPs) has been developed to treat different types of tumors. The Annona muricata plant is known for having anticancer activity. Its main compounds present in the leaves, stems and skin, allowing for its use as reducing agents. In this manuscript, AgNPs with leaf extract (AgNPs-LE) and fruit peel extract (AgNPs-PE) of A. muricata were biosynthesized obtaining an average nanoparticle diameter sizes smaller than 50 nm, being 19.63 ± 3.7 nm and 16.56 ± 4.1 nm, and with a surface plasmonic resonance (SPR) at 447 and 448 nm, respectively. The lactone functional group present in the LE and PE extracts was identified by the FTIR technique. The behavior and antiproliferation activity of AgNPs-LE and AgNPs-PE were evaluated in breast, colon and melanoma cancer cell lines. Our results showed that Annona muricata fruit peel, which is a waste product, has an antitumor effect more potent than leaf extract. This difference is maintained with AgNPs where the destruction of cancer cells was, for the first time, achieved using concentrations that do not exceed 3 μg/mL with a better therapeutic index in the different tumor strains. In conclusion, we present a low-cost one-step experimental setup to generate AgNPs-PE whose in-vitro biocompatibility and powerful therapeutic effect make it a very attractive tool worth exploiting.